Performance Study of the Francis Turbine Runner at Tanggari I Hydroelectric Power Plant via CFD and Reverse Engineer-ing - Achmad Walid; Irwanda Yuni Pungkiarto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the performance and conduct reverse engineering of the Francis Turbine runner at the Tanggari 1 Hydroelectric Power Plant (PLTA Tanggari 1) through 3D scanning and Computational Fluid Dynamics (CFD) simulation. The main objective is to evaluate the turbine's efficiency and identify areas for improvement in the runner geometry. Data from the 3D scan are used to reconstruct a CAD model, which is then numerically tested to predict hydraulic performance. CFD simulations are carried out under various guide vane openings and head variations. The simulation results show a maximum efficiency of 93% at a head of 122.4 meters with a guide vane opening angle of 26° and a flow rate of 8.5 m³/s. The resulting performance curve and hill chart indicate the optimal operating point or Best Efficiency Point (BEP), which serves as a critical reference for turbine operation settings. Flow phenomena such as separation and vortex formation were detected under off-BEP operating conditions, potentially causing pressure fluctuations and vibrations. As a technical recommendation, it is advised to operate the turbine close to the BEP to minimize vibrations and energy losses. Furthermore, the runner geometry obtained from reverse engineering can serve as a basis for component refabrication and the development of new runner designs that are more adaptive to varying load conditions.